Cytokine Storm in Coronavirus Disease 2019 and Adult-Onset Still’s Disease: Similarities and Differences - Meng, Jianfen; Ma, Yuning; Jia, Jinchao; Wang, Mengyan; Teng, Jialin; Shi, Hui; Liu, Honglei; Su, Yutong; Ye, Junna; Sun, Yue; Cheng, Xiaobing; Chi, Huihui; et al. (Frontiers in Immunology, 2021)
The catastrophic outbreak of coronavirus disease 2019 (COVID-19) is a public emergency nowadays. Adult-onset Still's disease (AOSD) is an autoinflammatory disease characterized by life-threatening complications. Systemic hyperinflammation and cytokine storm play a critical role in the pathogenesis of both COVID-19 and AOSD. We aimed to compare the similarities and differences focusing on ferritin and cytokine levels between severe COVID-19 and active AOSD. A literature search was performed using the databases PubMed, EMBASE, and Web of Science to collect the levels of cytokine including IL-1β, IL-6, IL-18, TNF-α, IL-10, and ferritin in severe COVID-19 patients. After extracting available data of indicators of interest, we acquired these statistics with a single-arm meta-analysis. Furthermore, a comparison was conducted between 52 patients with active AOSD in our center and severe COVID-19 patients from databases. The levels of IL-6 and IL-10 were higher in severe COVID-19 compared with that in active AOSD. There were no significant differences on the cytokine of IL-1β and TNF-α. Fold changes of IL-18 were defined as the mean expression level ratio of severe COVID-19 to healthy controls in the COVID-19 study and active AOSD to healthy controls in our study, individually. Although the fold change of IL-18 in patients with AOSD was significantly higher than patients with severe COVID-19 (fold change: 594.00 vs 2.17), there was no statistical comparability. In addition, the level of ferritin was higher in active AOSD in comparison with severe COVID-19. Our findings suggest that severe COVID-19 and active AOSD have differences in cytokine panel and ferritin level, indicating the pathogenic role of ferritin in overwhelming inflammation. And it paves the way to make efficacy therapeutic strategy targeting the hyperinflammatory process in COVID-19 according to AOSD management, especially in severe COVID-19.